In-vitro tolerance of Lasiodiplodia theobromae isolated from Musa paradisiaca and Rubus niveus to five fungicides of different mode of action - Jácome Quiroz, Luis Fernando (2024)
The dieback disease is caused by the phytopathogen Lasiodiplodia theobromae that affects farmer´s production; it is characterized by its ability to survive through pycnidia and chlamydospores in soil and crop residues, it spreads to plant tissues to remain endophytic until the host crop becomes vulnerable by mechanical damage or nutrient deficiency leading to death of young branches, mummification and fruit rot. Due to the persistent mode of L. theobromae, the research focused on the simultaneous depuration of strains of the phytopathogen isolated from banana and raspberry with the objective of detecting the mycelial growth rate against fungicides of different mode of action, establishing by means of a toxicity scale at one of the concentrations 10; 1; 0,1; 0,01 and 0,001 µg mL-1 as efficient with propiconazole, mancozeb, iprodione, difenoconazole and cyproconazole, respectively in their order. There was 100% growth inhibition with propiconazole and difenoconazole at a concentration of 10 µg mL-1 that allows them to be effective fungicides in the control of the phytopathogen, while mancozeb, iprodione and cyproconazole were harmless to L. theobromae, because they allowed its mycelial growth in the research.